Dėl E tipo ietigalių ornamentuotomis įmovomis chronologijos ir kilmės - Kazakevičius, Vytautas (Archaeologia Lituana, 1999)
Weapons have always been in the focus of attention of European archaeologists. As early as the beginning of 20th century several monographs were written which haven’t yet lost their importance and may be renderred among the classics of archaeological science. However, it must be admitted that the number of studies devoted to the most abounding type of weapons of the Iron Age – spears – is still insufficient. This is especially true about the spearheads found in the territory occupied by Baltic tribes. Investigators of Baltic tribes archaeology cannot boast of capital works or somewhat more exhaustive studies on spears. Only a few articles and chapters of some generalizing works are known which, however, are too short and abstract to satisfy the researchers specializing in certain types of weapons.This article devoted to a particular purpose: to discuss the problems of chronology and origin of E type (according to J. Petersen) spearheads with ornamented sockets from the Viking period.Two subtypes of E – type spearheads are found in the Baltic archaeological sites from the Viking period. Some of them have ornamented other ones – plain (without ornaments) sockets (Fig. 1). The ornament is composed of grooves arranged along the socket into arched lines which are brought together into one spot near the blade. On the opposite end these grooves form several arches (Fig. 2). This ornament is differently called by various authors: arched, Gothic, flame-shaped. It, presumably, serves only as a decoration and is not related with manufacturing technologies.Spearheads without decorated sockets make the absolute majority, whereas, those with arched-line ornament belongs to rarer finds. According to the available data 56 such spearheads were found in 26 archaeological sites (Fig. 3). Taking into consideration the present state and administrative boundaries 34 items were found in Lithuania, 6 – in Latvia and 16 E – type spearheads with decorated sockets found in the territory of former East Prussia. The given number might be not precise because it is difficult to count the finds from the East Prussia due to the lack of reliable data: records and literature. The largest number of such weapons – 14 – was uncovered in the Kaup bei Wiskiauten barrow cemetery. In other archaeological sites they were sparser: 5 spearheads in 4 graves of Upyna burial ground (Šilalė district), 4 – in Kretuonys barrow cemetery (Švenčionys district) (Fig. 9), 3 – in the Kapiņu Kristapēni burial ground (Preiladistrict), 2 spearheads in each were found in the Čiobiškis (Širvintos district) barrow cemetery, Marvelė (Kaunas) and Palanga burial grounds. It was a rare case when the Rupunionys (Kaunas district) hoards of weapons yielded two E – type spearheads with ornamented sockets (Fig. 4). In other Baltic archaeological sites such spearheads were uncovered isolated (Fig. 11) or stray finds (Fig. 5). The find spots of some other spearheads are not known.Not only ornaments but other weapons as well, uncovered in the same graves, are important in determining the chronology of E – type spearheads. These weapons include 196 swords, other types of spears, shield bosses and battle knives (1, 2 Tables). E – type spearheads with sockets decorated in arched-line ornament were found together with swords in 14 graves (Table 1). The H – type swords – found in 4 cases – were the most frequent finds. They were followed by V – type swords – in 3 graves – and swords of types B, E, K, M, Y, X – one find of each type. The B type sword is one of the earliest types of swords in the Viking period. It was found together with the discussed type of spearhead in grave No 124 (195) of Laiviai (Kretinga district) burial ground. In the Baltic territories these swords are dated to the end of 18th–9th C. A. D.Grave No 151a of Kaup bei Wiskiauten barrow cemetery which yielded a K – type sword with other artefacts (Fig. 6) is dated to the middle of 9th century. Graves from the 9th–10th centuries yielded also H, M, and Y types of swords. The latest E – type spearheads with ornamented sockets were uncovered in Kaup bei Wiskiauten and Palanga together with V and X types of swords and other artefacts (Fig. 7, 8).Among the ornaments which help to date the sets o(finds including the E – type socketed spearheads the most frequent are brooches: penannular with rolled, quadrangle and faceted terminals, sometimes ladder and cross-bow brooches with popy-head terminals, in rare cases – tortoise-shaped. “Warrior’s” bracelets serve as a good chronological indicator as well (Fig. 10).Thus, the archaeological material indicates that E – type socketed spearheads were included in the Baltic weaponry within the years 800–1050. At the beginning of 11th century such spearheads were rare exceptions.As to the origin of the E – type spearheads in the areas occupied by Balts there is an almost common oppinion that they came from Scandinavian lands where they were rather popular. Such oppinion is substantiated by archaeological data and circumstances of uncovering of these weapons. They prove that manufacturing centres of such weapons were situated in Scandinavia.As all imported weapons the E – type spearheads were very expensive and they did not play the role of “democratic” weapon in the Baltic weaponry. Not all members of society armed with such spearheads. They were possessed only by well-armed warriours. The statistical average of the set of weapons revealed that warriours possessing the E – type spearheads were also armed with a sword and another spear. Thus, we may conclude that E – type spearheads, as also swords, were included into the weaponry of professional warriours, i.e., persons who belonged to nobility.